2009
DOI: 10.1186/1755-8794-2-49
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of suitable endogenous reference genes for gene expression studies in human peripheral blood

Abstract: Background: Gene expression studies require appropriate normalization methods. One such method uses stably expressed reference genes. Since suitable reference genes appear to be unique for each tissue, we have identified an optimal set of the most stably expressed genes in human blood that can be used for normalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 39 publications
4
87
0
Order By: Relevance
“…However, there are several limitations and potential confounding factors. For example, although we have found that GAPDH mRNA expression in blood is stable in previous studies , replication of these biomarkers using several reference genes for normalization is desirable (Stamova, et al, 2009). In addition, differences in blood counts and PD medications may bias gene expression results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several limitations and potential confounding factors. For example, although we have found that GAPDH mRNA expression in blood is stable in previous studies , replication of these biomarkers using several reference genes for normalization is desirable (Stamova, et al, 2009). In addition, differences in blood counts and PD medications may bias gene expression results.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that these too can be affected by various experimental conditions and requires prior validation (Bionaz and Loor, 2007;Bustin, 2000;Chapman and Waldenström, 2015;Glare et al, 2002;Stamova et al, 2009). The present study found GAPDH to be a suitable endogenous in the SM and LT of young bulls, SM of steers and the LT of heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Six candidate reference genes (ACTB, CRY2, CSNK1G2, DECR1, FARP1, and TRAP1) that have been reported to be consistently expressed in human whole-blood samples were selected for investigation (11). The expression stability of the 6 reference genes in the training set were estimated using 4 commonly used algorithms: geNorm (12), NormFinder (13), BestKeeper (14), and the comparative cycle threshold (DC t ) method (15).…”
Section: Qrt-pcrmentioning
confidence: 99%